Legal bases of sports activity as an object of the theory of system organization - Maryna Korolova (Kharkiv State Academy of Physical Culture, 2019)
Today, the state of development of the sphere of physical culture and sports is characterized by the presence of organizational and legal problems at the level of functioning of all its components (physical education, professional or mass sport, etc.) on the way to solving socially significant social problems. The lack of an objective assessment of the current state of the public relations industry, which is covered by physical education and sports, taking into account the state policy of Ukraine's integration with the international community, leads to the process of assimilation of this industry in favor of a stronger partnership, which is being formed. Purpose: to analyze the activities of physical education and sports organizations from the position of conceptual provisions of the theory of system organization. Material & Methods: analysis of literary sources; analysis of documents; system analysis; historicism method; a method of analogy of observed patterns; mathematical modeling method. Results: the problem of managing complex social systems in the context of the functioning of the sports law industry is considered. The theoretical foundations of self-organization of collective interdependent relations in the field of physical culture are substantiated from the position of conceptual provisions of the theory of system organization. Conclusions: it has been established that at the present stage of development of public sports associations, the international sports movement and international sports federations, successful managerial activity can only be based on the condition that it is built on the basis of systems theory. It is established that the process of formation of interdependent relationships is based on the general principles of interaction of the object in question and its environment. It is the interaction of the object and the environment as a whole that acts as one of the determining principles of effective management and the key to maintaining the equilibrium state of the system.